NATIONAL LANGUAGE & MINORITY LANGUAGE RIGHTS - Faishal Zakaria (Englisia: Journal of Language, Education, and Humanities, 2016)
This brief paper highlights the perspectives of those proposing and opposing the idea of Minority Language Right (MLR). Then, the paper relates this discussion to the context of bi/multilingualism in Indonesia by referring to cases of bi/multilingualism in different contexts. In particular, it is also discussed whether MLR is relevant to Indonesian, a national language of Indonesia, seen through historical, political, social, and economic perspectives of bi/multilingualism in Indonesia. In the end, the author’s stance of MLR is asserted.